2001
DOI: 10.1039/b101985f
|View full text |Cite
|
Sign up to set email alerts
|

The Mills–Nixon effect and chemical reactivity—methyl cation affinity of some cycloalkabenzenes

Abstract: The problem of the methyl cation attack on carbon atoms belonging to the benzene moiety fused to small rings is explored by the ab initio models at the MP2 level of sophistication. It is shown that the β-position is more reactive than the α-site in kinetically controlled reactions, which is in accordance with the original Mills-Nixon postulate. On the other hand, it appears that in thermodynamically controlled electrophilic substitution reactions the α-site should be slightly preferred for three-, four-and fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…It has also been argued, for example, that 4,5-bis(dimethylamino)fluorene is a stronger base than DMAN, due to the increased hydrogen-bond strength. [38] Interestingly, disubstitution of guanidine groups in 5 does introduce some bond alternation in the benzene fragments. In order to get an understanding of the structural properties of 5 and 5 p, one considers first the geometrical characteristics of the parent molecule fluorene 4.…”
mentioning
confidence: 99%
“…It has also been argued, for example, that 4,5-bis(dimethylamino)fluorene is a stronger base than DMAN, due to the increased hydrogen-bond strength. [38] Interestingly, disubstitution of guanidine groups in 5 does introduce some bond alternation in the benzene fragments. In order to get an understanding of the structural properties of 5 and 5 p, one considers first the geometrical characteristics of the parent molecule fluorene 4.…”
mentioning
confidence: 99%
“…Based on the observed distributions and calculated thermochemical data, it was concluded that: (i) CH 5 ϩ reacts via proton transfer to the C᎐ ᎐ C bond to give alkyl cations or via hydride-ion abstraction to yield alkenyl ions; (ii) C 2 H 5 ϩ reacts via proton transfer to the C᎐ ᎐ C bond to give alkyl cations or via alkanide-ion abstraction to yield alkenyl ions; and (iii) C 3 H 5 ϩ ions undergo addition to the C᎐ ᎐ C bond. A theoretical study on the attack of CH 3 ϩ at carbon atoms of a benzene moiety fused to small rings 79 follows the first experimental examination of the Mills-Nixon (MN) effect discussed in last year's review. In kinetically controlled reactions the β-position is more reactive than the α-site, supporting the original Mills-Nixon postulate.…”
Section: A Carbocation Ion-molecule Reactionsmentioning
confidence: 99%
“…Both of these effects are exciting to the organic chemistry community. The fused small rings are known to influence the reactivity and regioselectivity within the aromatic fragment …”
Section: Introductionmentioning
confidence: 99%